2020
DOI: 10.1167/iovs.61.5.22
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glial Fibrillary Acid Protein and Vimentin in Vitreous Fluid as a Biomarker for Proliferative Vitreoretinopathy

Abstract: Glial fibrillary acid protein (GFAP) and vimentin are type III intermediate filament proteins, ubiquitously expressed in retinal glial cells. Under retinal stress, both GFAP and vimentin are well-known sensitive markers for retinal gliosis. However, little is known about whether these proteins are released into the vitreous body in response to retinal gliosis or are related to the severity of retinal gliosis seen in proliferative vitreoretinopathy (PVR). METHODS. Vitreous fluids were collected from 44 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…Interestingly, we have shown previously that astrocytes lacking functional βA3/A1-crystallin proliferate and migrate abnormally into the vitreous and ensheath the hyaloid artery, thereby contributing to persistent fetal vasculature (PFV) disease 69 . However, it has been previously shown that the GFAP levels were higher in subjects with retinal detachment, proliferative vitreoretinopathy or epiretinal gliosis 67 , 68 . Studies in rabbits have demonstrated that the astrocytes are separated from the vitreous by a thin basement membrane of the inner limiting membrane and any disruption or gaps in the latter would allow the contact between astrocytes and vitreous body 70 , thereby suggesting that astrocyte numbers would increase in the vitreous humor of an eye with retinal disease such as DR. Further, we observed that DR patients with the highest PTP1B/βA1 ratios also had higher levels of pro-inflammatory factors in their vitreous.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we have shown previously that astrocytes lacking functional βA3/A1-crystallin proliferate and migrate abnormally into the vitreous and ensheath the hyaloid artery, thereby contributing to persistent fetal vasculature (PFV) disease 69 . However, it has been previously shown that the GFAP levels were higher in subjects with retinal detachment, proliferative vitreoretinopathy or epiretinal gliosis 67 , 68 . Studies in rabbits have demonstrated that the astrocytes are separated from the vitreous by a thin basement membrane of the inner limiting membrane and any disruption or gaps in the latter would allow the contact between astrocytes and vitreous body 70 , thereby suggesting that astrocyte numbers would increase in the vitreous humor of an eye with retinal disease such as DR. Further, we observed that DR patients with the highest PTP1B/βA1 ratios also had higher levels of pro-inflammatory factors in their vitreous.…”
Section: Discussionmentioning
confidence: 92%
“…One of the notable observations in our study was that vitreous samples obtained from human PDR patients showed increased numbers of astrocytes (CD11b − Glast1 + ). Presence of GFAP, a marker for glial cells including astrocytes in the vitreous humor homogenates of human cadaveric donor controls and subjects with macular hole or epiretinal membrane suggests the presence of astrocytes in normal vitreous humor 67 , 68 . Interestingly, we have shown previously that astrocytes lacking functional βA3/A1-crystallin proliferate and migrate abnormally into the vitreous and ensheath the hyaloid artery, thereby contributing to persistent fetal vasculature (PFV) disease 69 .…”
Section: Discussionmentioning
confidence: 99%
“…RPE 是一层立方形上皮细胞,其一侧与感光细胞紧密相连,另一侧与 Bruch`s 膜相连。视网膜色素上皮细胞主要参与光吸收、视色素循环、营养物质 和离子转运及感光细胞外节吞噬等视网膜生理过程,是视网膜代谢微环境稳态 的关键细胞,同时也参与了视网膜免疫豁免微环境的构建 [52] 。 2.1.3 视网膜胶质细胞 视网膜包含三种类型的胶质细胞:大胶质细胞(Müller 胶质细胞、星形胶质 细胞)和小胶质细胞。三种胶质细胞不仅提供结构上的支持,而且通过调节新 陈代谢、吞噬神经元碎片、参与神经递质循环和营养因子的释放,参与维持视 网膜复杂的微环境稳态 [5,11] 。 Müller 细胞起源于神经视网膜,呈放射状横跨整个神经视网膜,参与形成 神经视网膜的内外界膜,支撑视网膜结构,同时也搭建了视网膜神经元、血管 和玻璃体之间的解剖联系 [5] 。除了结构支持,Müller 细胞还参与视网膜营养代 谢、维持离子平衡和神经递质的循环。Müller 胶质细胞具有吞噬功能,能够吞 噬清除视网膜死亡神经元和碎片,从而维持视网膜微环境稳态 [53] 。此外, Müller 细胞在视网膜免疫微环境稳态和促神经再生微环境形成中也发挥重要作 用 [5,54] 。 起源于中枢神经系统的星形胶质细胞沿视神经迁移至视网膜,主要位于视 网膜神经节细胞层和神经纤维层,它们的突起覆盖视网膜血管表面形成视网膜 血管内屏障 [55,56] 。星形胶质细胞在微环境的离子稳态维持、神经元信号传导和 视网膜内皮屏障的形成中起着关键作用 [55] 。和 Müller 细胞类似,星形胶质细胞 也具备吞噬能力,通过吞噬轴突和细胞器来维持细胞外环境稳态 [57] 。 小胶质细胞是视网膜中的唯一原位免疫细胞,被认为起源于胚胎卵黄囊的 原始巨噬细胞,而后迁移定植于视网膜。在视网膜发育期,小胶质细胞在控制 发育相关的细胞凋亡、血管生成和突触修饰等方面,起着至关重要的作用 [58] 。 在成年期,静息态小胶质细胞主要定位于视网膜内、外丛状层,细胞体小呈圆 形,周围有许多分支。小胶质细胞具有对外界环境较高的敏感度和可塑性,能 够积极地与视网膜神经元和大胶质细胞进行通讯,监视周围环境并做出反应, 对维持视网膜微环境稳态方面发挥着至关重要的作用 [11] 。 1.2 细胞外基质 细胞外基质是由细胞分泌到细胞外的蛋白形成的三维结构,在结构和功能 上支持细胞和组织 [59] [5] 。在损伤早期,Müller 细 胞激活后能分泌营养因子和抗氧化物质以修复损伤的视网膜 [61] 。研究提示, Müller 细胞在视网膜变性早期也能通过吞噬作用清除死亡的感光细胞 [62] 。随着 损伤进展,Müller 细胞的持续激活会释放有害因子,进一步加剧神经元的损伤 和阻碍受损视网膜组织的再生 [63] 。同时,增生的 Müller 细胞在视网膜下腔形成 胶质瘢痕,阻止向视网膜神经元的营养物质输送 [64,65] 。除此之外,Müller 细胞 反应性增生还会导致玻璃体视网膜增殖,进一步导致视网膜脱离 [66] 。反应性增 生的 Müller 细胞也能产生趋化因子或者作为迁移支架促进单核巨噬细胞/小胶质 细胞的浸润,进一步加剧视网膜变性 [63,67] 。 1.1.1 物理屏障 视网膜 Müller 细胞过度激活形成的胶质瘢痕可作为物理屏障阻碍移植细胞 的迁移和整合。研究表明,无论是采用视网膜片还是细胞悬液方式进行细胞移 植时,Müller 细胞的过度激活都会影响移植供体中的细胞向视网膜内迁移,导 致移植细胞的整合率降低 [47,64] 。另外,移植时受者动物的年龄及视网膜变性的 病变阶段也可以影响植入细胞的整合效率,可能是因为老年或变性晚期视网膜 胶质细胞增生形成胶质疤痕,阻碍了植入细胞的整合 [68] 。如果调整视网膜变性 鼠中 Müller 细胞反应蛋白 GFAP 的表达量,感光前体细胞移植后的整合率与 GFAP 表达水平呈显著的负相关 [68,69] 。不容忽视的是,Müller 细胞支撑整个视 网膜并且其足突与感光细胞内节形成紧密连接,组成了视网膜外界膜。当采用 GFAP -/ -Vim -/ -敲除鼠清除小鼠 Müller 细胞,导致视网膜细胞原本由 Müller 占据 的间隙产生和外界膜的破坏后,可提高移植入视网膜细胞的整合 [69,70] 。研究证 实,当视网膜外界膜的完整性被破坏时,整合的感光细胞数量显著增加 [51] 。 1.1.2 化学屏障 此外,当 Müller 细胞反应性增生时,可...…”
Section: Rpeunclassified
“…In diabetic retinopathy, Müller cells show morphologic changes, such as hypertrophy, associated with GFAP production [ 25 ]. This is a remarkably ubiquitous response that can be observed in some forms of retinal stress, damage, and degeneration, including retinal detachment and retinal photocoagulation [ 26 , 27 ]. Moreover, the presence of GFAP in body fluids has already been reported and proposed as a biomarker of glial activation and pathology in neurological diseases [ 27 , 28 ].…”
Section: Intraocular Samplingmentioning
confidence: 99%
“…This is a remarkably ubiquitous response that can be observed in some forms of retinal stress, damage, and degeneration, including retinal detachment and retinal photocoagulation [ 26 , 27 ]. Moreover, the presence of GFAP in body fluids has already been reported and proposed as a biomarker of glial activation and pathology in neurological diseases [ 27 , 28 ]. It has been reported that the modifications and alteration of Müller cell triggers cellular proteolysis.…”
Section: Intraocular Samplingmentioning
confidence: 99%